Factors associated with eclampsia among women who gave birth at Adama hospital medical college, Adama, Ethiopia: A case control study: Factors Associated with Eclampsia - Tegene, Dereje; Mannekulih, Ephrem; Garoma, Sileshi (Ethiopian Journal of Reproductive Health, 2025)
Background: Eclampsia is defined as the occurrences of convulsions and/ or unexplained coma in women with signs and symptoms of preeclampsia. Eclampsia is an obstetric emergency associated with increased maternal and perinatal mortality and morbidity. Identification of predictive factors associated with eclampsia helps caregivers for early identification and prioritization of high-risk pregnant women, which in turn help to develop preventive strategy; in this regard, there is limited information. Objective: The study aimed to identify factors associated with Eclampsia among women who gave birth at Adama hospital medical college from January 2019 to December 2021. Methods and Materials: A case-control study was conducted by reviewing data from a total of 467 patient charts (94 cases and 373 controls). Data were entered into Epi info-7.2 and then exported to SPSS version 20 for analysis. Binary logistic regression analysis was used to model the association between independent variables and Eclampsia. The association between the predictor variables and eclampsia was estimated using an odds ratio with a 95% confidence interval. Results: The odds of having eclampsia were 5.3-fold higher among rural residents (AOR = 5.30; 95% CI: 2.98, 9.41). The odds of developing eclampsia were 3.86 fold higher in primiparous (AOR = 3.86; 95% CI: 2.06, 7.24). Women with no antenatal care follow-up had 6.3-fold higher odds of eclampsia (AOR = 6.30; 95% CI: 2.75, 14.46). The odds of eclampsia among anemic pregnant women were 2.3-fold higher (AOR = 2.29; 95% CI: 1.25, 4.18). The odds of eclampsia were 4.7 fold higher in a pregnant woman with a urinary tract infection (AOR = 4.70; 95% CI: 2.41, 9.16). Conclusion: Being a rural resident, being primigravida, having no antenatal care follow-up, the presence of anemia, and urinary tract infection was independent determinant of eclampsia.